The Factors Influencing Grade VIII Students’ Verbal Participation In English Class - Stakisia Puteri Pradestina; Atalya Agustin (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This study was held to identify the factors behind students’ lack of verbal participation in English class. This research was a qualitative case study research, with 26 students of grade VIII at one private school in Jakarta as the subject of research. The instrument used was questionnaire which analyzed using thematic-analysis method. The results showed there are five factors influencing students’ lack of verbal participation. It started from teacher’s personality that makes the students having lack of self-efficacy in English lesson, lack of self-confidence in speaking English, lack of preparation before the English class begins, and the fear of making mistakes and being laughed at by others. This study also suggested some teaching strategies that could be used by the teachers to improve students’ verbal participation in English class or to overcome the factors behind students’ lack of verbal participation, such as Inquiry-Based Learning (IBL), Contextual Teaching Learning (CTL), and Cooperative Learning (CL).